Comprehensive genomic diagnosis of non-syndromic and syndromic hereditary hearing loss in Spanish patients - Rubén Cabanillas; Marta Diñeiro; Guadalupe A. Cifuentes; David Castillo; Patricia C. Pruneda; Rebeca Álvarez; Noelia Sánchez-Durán; Raquel Capín; Ana Plasencia; Mónica Viejo-Díaz; Noelia García-González; Inés Hernando; et al. (BMC, 2018)
Abstract Background Sensorineural hearing loss (SNHL) is the most common sensory impairment. Comprehensive next-generation sequencing (NGS) has become the standard for the etiological diagnosis of early-onset SNHL. However, accurate selection of target genomic regions (gene panel/exome/genome), analytical performance and variant interpretation remain relevant difficulties for its clinical implementation. Methods We developed a novel NGS panel with 199 genes associated with non-syndromic and/or syndromic SNHL. We evaluated the analytical sensitivity and specificity of the panel on 1624 known single nucleotide variants (SNVs) and indels on a mixture of genomic DNA from 10 previously characterized lymphoblastoid cell lines, and analyzed 50 Spanish patients with presumed hereditary SNHL not caused by GJB2/GJB6, OTOF nor MT-RNR1 mutations. Results The analytical sensitivity of the test to detect SNVs and indels on the DNA mixture from the cell lines was > 99.5%, with a specificity > 99.9%. The diagnostic yield on the SNHL patients was 42% (21/50): 47.6% (10/21) with autosomal recessive inheritance pattern (BSND, CDH23, MYO15A, STRC [n = 2], USH2A [n = 3], RDX, SLC26A4); 38.1% (8/21) autosomal dominant (ACTG1 [n = 3; 2 de novo], CHD7, GATA3 [de novo], MITF, P2RX2, SOX10), and 14.3% (3/21) X-linked (COL4A5 [de novo], POU3F4, PRPS1). 46.9% of causative variants (15/32) were not in the databases. 28.6% of genetically diagnosed cases (6/21) had previously undetected syndromes (Barakat, Usher type 2A [n = 3] and Waardenburg [n = 2]). 19% of genetic diagnoses (4/21) were attributable to large deletions/duplications (STRC deletion [n = 2]; partial CDH23 duplication; RDX exon 2 deletion). Conclusions In the era of precision medicine, obtaining an etiologic diagnosis of SNHL is imperative. Here, we contribute to show that, with the right methodology, NGS can be transferred to the clinical practice, boosting the yield of SNHL genetic diagnosis to 50-60% (including GJB2/GJB6 alterations), improving diagnostic/prognostic accuracy, refining genetic and reproductive counseling and revealing clinically relevant undiagnosed syndromes.